Imaging features of marginal ulcers on multidetector CT. Issue 3 (March 2023) - Zulfiqar, M.; Ludwig, D.R.; Strnad, B.; McVay, M.; Rengarajan, A.; Kushnir, V.; Mellnick, V.
Abstract : AIM: To assess the inter-reader agreement and frequency of various imaging findings of marginal ulcers on computed tomography (CT) in a series of patients with endoscopically or surgically confirmed marginal ulcer disease. MATERIALS AND METHODS: This was a institutional review board-approved retrospective analysis involving a single academic institution. Eighty patients with a gastro-enteric anastomosis with confirmed marginal ulcer on endoscopy or surgery and multidetector (MD)CT performed within a month reviewed by two fellowship-trained abdominal radiologists to assess for the presence or absence of predetermined imaging characteristics categorised under signs of inflammation, signs of penetration, signs of perforation, and signs of obstruction. Inter-rater reliability was assessed using the Cohen kappa test. RESULTS: Findings of perforation had moderate to substantial agreement, including the presence of extraluminal air, extraluminal fluid, and leakage of oral contrast medium (kappa 0.83 [0.61, 1.05], 0.57 [0.35, 0.79] and 0.75 [0.18, 1.31], respectively) although these were present relatively infrequently (23–26%, 30–43%, 3–4%, respectively). Additional imaging characteristics with moderate agreement were the presence of perienteric fat stranding, a dilated stomach proximal to the anastomosis, and penetration into adjacent organ (kappa 0.45 [0.23, 0.69], 0.47 [0.26, 0.69], and 0.47 [0.25, 0.69], respectively) which were variably present (80–88%, 11–16%, 5%, respectively). Wall thickening and contour abnormalities, although frequently present (61–90% and 60–80%, respectively) had only slight to fair agreement (kappa 0.09 [–0.14, 0.30] and 0.29 [0.07, 0.51]). CONCLUSION: Signs of perforation have high inter-reader agreement but occur relatively infrequently. Fat stranding, wall thickening, and contour abnormalities are much more common; however, only fat stranding had moderate agreement. Highlights: Marginal ulcers occur as a late complication after gastro-enteric anastomosis. CT signs are sorted as inflammation, penetration, obstruction and perforation. Signs of perforation though infrequent, had high inter-reader agreement. Signs of inflammation were more common. Only fat stranding had moderate agreement. Oral contrast when present may help in delineating site of perforation.